Responding to Gender-based Violence in Scotland: The Scope of the Gender Equality Duty to Drive Cultural and Practical Change - Burman, M. (2010)
This piece of research has its roots in well-established policy debates in Scotland. Following the passage of the Criminal Justice (Scotland) Act 2003, which introduced a new statutory aggravation for crimes motivated by religious prejudice, the then Scottish Executive convened a working group to explore and make recommendations on whether there was a case for similar provision for other social groups. The report and recommendations of the Hate Crime Working Group, published in 2004, recognised that the debate to introduce gender aggravation was one of the most contested issues which it had looked at, but it did not believe that at that stage it could recommend introducing such a provision. These debates re-emerged with Patrick Harvie’s member’s bill which was to become the Offences (Aggravation by Prejudice) (Scotland) Act 2009. The Equality and Human Rights Commission, along with many organisations in the women’s sector in Scotland, stated in its evidence on the bill that it did not believe that a statutory gender aggravation would be an effective additional criminal justice response to identifying and tackling crime motivated by gender prejudice. This of course begs the question about what is required to better address these types of crime. This piece of research, undertaken for the EHRC by the Scottish Centre for Crime and Justice Research, aims to be a useful contribution to this debate. It explores some of the arguments for and against a gender aggravation in Scots criminal law before considering the evidence thus far of the impact the Gender Equality Duty (GED) has had on Scotland’s criminal justice system, and makes a number of useful recommendations for the future. The EHRC subscribes to a gendered model of violence against women, which sees it as both a cause and consequence of wider gender inequality. We hope this report can help inform ongoing policy debate on criminal justice agencies’ response to violence against women, particularly in light of the new single equality duty which Scottish Ministers will in due course place on Scottish public authorities under powers conferred on them by the Equality Act 2010. We believe that the appropriate regulatory framework for public bodies working in this area is one of the prerequisites for further improving on Scotland’s record of identifying and tackling gender-based crime